2014
DOI: 10.1063/1.4866187
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic control of ferroelectric polarization in a self-formed single magnetoelectric domain of multiferroic Ba3NbFe3Si2O14

Abstract: We have discovered strong magnetoelectric (ME) effects in the single chiral-helical magnetic state of single-crystalline langasite Ba 3 NbFe 3 Si 2 O 14 that is crystallographically chiral. The ferroelectric polarization, predominantly aligned along the a axis below the Nèel temperature of ~27 K, changes in a highly non-linear fashion in the presence of in-plane magnetic fields (H) perpendicular to the a axis (H//b*). This ME effect as well as smaller ME effects in other directions exhibit no poling dependence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…In particular, Ba 3 NbFe 3 Si 2 O 14 single crystals have been shown to possess a rather unique antiferromagnetic structure below T N ¼26 K [8] with single domain helicity and triangular chirality. In addition to this, Ba 3 NbFe 3 Si 2 O 14 exhibits ferroelectricity developing near T N [15,16]. This property is particularly striking as no symmetry loss from the P321 space group can be detected within the resolution of conventional methods such as diffraction [17].…”
Section: Introductionmentioning
confidence: 91%
“…In particular, Ba 3 NbFe 3 Si 2 O 14 single crystals have been shown to possess a rather unique antiferromagnetic structure below T N ¼26 K [8] with single domain helicity and triangular chirality. In addition to this, Ba 3 NbFe 3 Si 2 O 14 exhibits ferroelectricity developing near T N [15,16]. This property is particularly striking as no symmetry loss from the P321 space group can be detected within the resolution of conventional methods such as diffraction [17].…”
Section: Introductionmentioning
confidence: 91%
“…It was demonstrated that the structure of langasites above T N becomes both paramagnetic and paraelectric. A considerable current interest is attracted to the problem of the crystallo graphic [15] and magnetic chiralities [16][17][18] in these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…This has been confirmed by recent polarization studies which show the presence of intrinsic electric polarization in the compound. The intrinsic polarization present in the absence of a magnetic field has been found to reverse its direction with increasing magnetic field24.…”
mentioning
confidence: 96%